2021
DOI: 10.13052/ijfp1439-9776.2224
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effective Electro-Hydraulic Actuator Solution with Open Circuit Architecture

Abstract: With the recent electrification trend in the fluid power area, more research has been incentivized to propose cost-effective and energy-efficient solutions for hydraulic systems. Hence, electro-hydraulic actuator (EHA) architectures receive increasing attention. The paper proposes a novel open-circuit EHA architecture, with the goal to obtain a cost-effective solution for mobile applications while maximizing the overall system efficiency. The proposed EHA is capable of meeting or exceeding traditional off-road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Table 3 summarizes the parameters of the reference application, which is the boom cylinder used on a compact loader, as shown in Figure 9. The sizing methods are detailed in previous works of the authors as [14] and [15]. The maximum load force generates a pressure of 120 bar, while the system components are selected for extreme conditions up to 210 bar (e.g., relief valve), and the continuum pressure of the EHU is up to 120 bar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes the parameters of the reference application, which is the boom cylinder used on a compact loader, as shown in Figure 9. The sizing methods are detailed in previous works of the authors as [14] and [15]. The maximum load force generates a pressure of 120 bar, while the system components are selected for extreme conditions up to 210 bar (e.g., relief valve), and the continuum pressure of the EHU is up to 120 bar.…”
Section: Methodsmentioning
confidence: 99%
“…This paper, instead, focuses on the performance of the hydraulic system in combination with the EHU. The hydraulic system under study in this work builds upon previous work on a four-quadrant EHA developed by the authors [12][13][14]. In previous studies, the energy performance was studied in terms of the four-quadrant EHA using commercial drives [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another group of experimental studies can be identified in which the implemented hardware is limited to the power-train, including the cylinders, and the load force is emulated by applying weights or force from load cylinders. Two examples of this are [14], where static load conditions of a skidder are simulated by lifting and lowering different weight plates, and in [15], another hydraulic cylinder is used to apply a load to the tested cylinder, which the authors mention as a way of testing the performance in a realistic duty cycle. Such an approach might be sufficient to evaluate the static efficiencies of a single actuator, but realistic cycles with multiple mutually influencing actuators and realistic inertia for dynamic investigations cannot be tested.…”
Section: Experimental Approaches In Literaturementioning
confidence: 99%
“…Furthermore, the efficiency or consumption of the whole implement system with all major actuators is of interest; thus, boom, tilt, and telescope cylinders should be present in the setup connected by the real kinematic chains. Accordingly, setting up a test rig for a single actuator as in [14][15][16][17], would not be effective. Instead, an existing conventional nine-tonne telehandler has been chosen as the test platform, which can be seen in Figure 1, to incorporate the original kinematic chains, inertia, and control interface.…”
Section: Chosen Experimental Design For Rapid Yet Realistic Testingmentioning
confidence: 99%
“…For such drives, the cost of electric components may be considered a challenge for their broad application, and this has been addressed e.g., via component downsizing approaches. These include the use of hydraulic energy storages [38] and the use of valves enabling flow regenerative functionalities [39][40][41][42]. Comprehensive reviews on developments of such types of drives are available in [43,44].…”
Section: Introductionmentioning
confidence: 99%